POLITIK DOMINASI KELUARGA AL-SAUD DALAM KERAJAAN SAUDI ARABIA (1932 – 2008) - Anwar Nuris (Jurnal Tamaddun, 2022)
Saudi Arabia is an absolute monarchy that places a king from the descendants of Abdul Aziz bin Abdurahman al-Saud (d. 1953) as the highest authority in government. At another level, apart from the position of king, positions such as prime minister, vice prime minister, minister of defence, minister of interior, commander of the national army, head of intelligence, governor, and other important positions within departments are positions reserved for princes from the al-Saud lineage. This kind of condition then makes the domestic political dynamics of the Kingdom of Saudi Arabia as part of the implementative dynamics of “family” internal politics. Despite being abandoned by its first initiators, the domination politics of the al-Saud family continued to survive until the latest developments in the Kingdom of Saudi Arabia. Besides that, recently the Allegiance Commission was formed in 2006 its task is to regulate the succession of power in the Kingdom of Saudi Arabia, where all of its members are princes from the al-Saud dynasty. Therefore the politics of the al-Saud family in the Kingdom of Saudi Arabia are increasingly gaining dominance momentum.